Soil investigation dutch penetration test implementation of North Sumatra Polda Flat Houses - Suita, Diana; Simanjuntak, Johan Oberlyn; Lubis, Muhammad Yusuf Parlagutan; Simorangkir, Simon Petrus (Jurnal VORTEKS, 2024)
From the results of drilling tests with machine drills, standard penetration tests (SPT), and DCPT or sondir tests, several conclusions can be taken as follows: 1). The results of boring tests show that the soil layer has medium soil consistency at a depth of 0 - 9.85 meters with NSPT value 10 – 30. 2). The soil layer consists of sandy clay, fine sand pumice stone, and fine sand. 3). Test results for the depth of solid soil at a depth of 18.6 – 19.00 meters. 4. The cone tip resistance at point S-01 is 200 kg/cm2 and S-02 is 173 kg/cm2 5). Calculation of the vertical Bearing Capacity (Qi) of the pile foundation from SPT data using a safety factor for tip penetration resistance = 3, for sticky resistance used = 5. 6). For large construction loads using deep foundations, it is necessary to check to a depth of > 10 meters or attain NSPT 60 in a row 3 times